Orchestrating Circular Ecosystems : A Systematic Literature Review - Kontula, Nelle (My University, 2026)
The aim of the circular economy is to improve resource efficiency, extend the use of materials, and minimize waste. It requires a shift from linear production and consumption models toward closed-loop systems, where value is maintained for as long as possible. This transition emphasizes collaboration between different actors and makes the ecosystem perspective increasingly important. At the same time, managing ecosystems becomes more important, but also more challenging. This study examines ecosystem orchestration, particularly in the context of the circular economy. As the business environment becomes more networked and involves multiple actors, value creation increasingly relies on collaboration and the alignment of resources between actors. Although the ecosystem concept has become central in business research, the management of ecosystems remain partly unclear. The concept of orchestration helps to address this issue. The aim of this study is to clarify how ecosystem orchestration is understood in the literature and how this understanding changes in circular ecosystems. The study adopts a systematic literature review (SLR) approach. The data consists of peer-reviewed academic articles collected from the Web of Science and Scopus databases. The final dataset includes 25 selected studies in which ecosystem orchestration plays a central role. The data is analyzed by focusing on three key dimensions: who orchestrates, what is orchestrated, and how orchestration is carried out. The findings show that ecosystem orchestration is not the responsibility of a single actor. Instead, it is carried out by different actors, such as focal firms, multiple actors, and public or neutral organizations. Orchestration targets both networks and resources, but also extends to system-level elements such as value propositions and institutional structures. In addition, orchestration logic often appears as a hybrid, combining deliberate direction with continuous adaptation and interaction. In circular economy ecosystems, orchestration is more distributed, more dynamic, and more dependent on the alignment of multiple actors than in traditional ecosystems. This suggests that existing orchestration theories should be further developed to better reflect the complex and cross-sectoral nature of circular economy environments. This study contributes to the theoretical understanding of ecosystem orchestration by structuring the concept through clear dimensions and by extending this understanding to the context of circular economy ecosystems.
Keywords: circular economy; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|